(untitled) (World Conference on Agricultural and Earth Sciences, 2026)
The efficiency of cost management in higher educational institutions has become a central concern for policymakers, administrators, and stakeholders worldwide. Rising operational expenses, expanding student populations, and the growing complexity of academic programs have placed significant financial pressures on universities. In this context, mechanisms for assessing and optimizing cost efficiency are crucial to ensure the sustainable functioning of higher education institutions while maintaining high standards of teaching and research.